Does a Rapid Decline in the Hematological and Biochemical Parameters Induced by Interferon and Ribavirin Combination Therapy for the Hepatitis C Virus Predict a Sustained Viral Response? - Christian Turbide; Constantine A Soulellis; Marc Deschênes; Nir Hilzenrat (Canadian Journal of Gastroenterology)
BACKGROUND AND OBJECTIVES: To analyze whether rapid myelosuppression and a decrease in alanine aminotransferase (ALT) induced by standard interferon (IFN) and ribavirin (RBV) combination therapy predict a sustained viral response (SVR) in hepatitis C virus patients.